A Study of the Promotion of Environmentally Friendly Agriculture in China - Ma, Jian (WILAYAH: The International Journal of East Asian Studies, 2014)
The comprehensive production capacity of China’s agriculture had unprecedently enhanced since the economic reforms and implementation of the household contract responsibility system since the 1980s. In order to ensure food security of more than 1.3 billion Chinese and to make the sure quantity of food increases, a large number of chemical fertilizers and pesticides have been used in China’s agricultural production. While this played a positive role to improve food quantity, it also led to the serious problems of environmental pollution and low food quality. For the purpose of realizing sustainable agriculture development and satisfying consumers’ requirement for high quality and safety in agricultural products, the environmentally friendly agriculture reform was popularized in the 1990s as an important part of China’s agriculture production. By examining the status and existing problems, this article will discuss the promotion of environmentally friendly agricultural in China.